Visualization of cross‐resistance between antimicrobial agents by asymmetric multidimensional scaling. (24th November 2021) - Hatsuda, Yasutoshi; Maki, Syou; Ishizaka, Toshihiko; Omotani, Sachiko; Koizumi, Naonori; Yasui, Yukako; Saito, Takako; Myotoku, Michiaki; Okada, Akinori; Imaizumi, Tadashi
Abstract: What is known and objective: In our previous studies, we developed a cross‐resistance rate (CRR) correlation diagram (CRR diagram) that visually captures the magnitude of CRRs between antimicrobials using scatter plots. We used asymmetric multidimensional scaling (MDS) to transform cross‐resistance similarities between antimicrobials into a 2‐dimensional map and attempted to visually express them. We also explored the antibiograms of Pseudomonas aeruginosa before and after the transfer to newly built hospitals, and we determined by the CRR diagram that the CRRs among β‐lactam antimicrobials other than carbapenems decreased substantially with the facility transfer. The present study tests whether the analysis of CRRs by asymmetric MDS can be used as new visual information that is easy for healthcare professionals to understand. Method: We tested the impact of changes in the nosocomial environment due to institutional transfers on CRRs among antimicrobials in asymmetric MDS, as well as contrasted the asymmetric MDS map and CRR diagram. Results and Discussion: In the asymmetric MDS map, antimicrobial groups with the same mechanism of action were displayed close together, and antimicrobial groups with different mechanisms of action were displayed separately. The asymmetric MDS map drawn solely for antimicrobials belonging to the group with the same mechanism of action showed similarities to the CRR diagram. Also, the distance of each antimicrobial to other antimicrobials shown in the asymmetric MDS map was negatively correlated with the CRRs for them against that antimicrobial. What is new and conclusion: The asymmetric MDS map expresses the dissimilarity as distances between agents, and there are no meanings or units on the ordinate and abscissa axes of the output map. In contrast, the CRR diagram expresses the antimicrobials' resistance status as values, such as resistance rate and CRR. By analysing the CRRs in the asymmetric MDS, it is feasible to visually recognize cross‐resistance similarities between antimicrobial groups as distances. The use of the asymmetric MDS combined with the CRR diagram allows us to visually understand the resistance and cross‐resistance status of each antimicrobial agent as a 2‐dimensional map, as well as to understand the trends and characteristics of the data by means of quantitative values. Abstract : By analysing the CRRs in the asymmetric MDS, it is feasible to visually recognize cross‐resistance similarities between antimicrobialgroups as distances.